2019
DOI: 10.5430/ijfr.v10n3p51
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Governance Attributes in Fraud Detterence

Abstract: The failures of corporations such as Enron, WorldCom and HIH Insurance, to name but a few, have heightened investor awareness of the need to not only evaluate company performance, but also to consider the possibility that financial statements may not be a true reflection of company results, as fraudulent activities may have occurred during the reporting period. Since parties who are outside of the firm do not have access to pertinent information, they have to rely upon published financial and non-financial dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 43 publications
3
12
0
1
Order By: Relevance
“…The probit regression results did not reveal such an impact of the incidences of corporate fraud; thus, H04 is failed to be rejected. This result is consistent with the findings of Chen et al (2006), Shan et al (2013), Salleh and Othman (2016) and Sadique et al (2019). This result indicates that CEO duality may not be a significant factor in influencing corporate fraud.…”
Section: Findings and Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…The probit regression results did not reveal such an impact of the incidences of corporate fraud; thus, H04 is failed to be rejected. This result is consistent with the findings of Chen et al (2006), Shan et al (2013), Salleh and Othman (2016) and Sadique et al (2019). This result indicates that CEO duality may not be a significant factor in influencing corporate fraud.…”
Section: Findings and Discussionsupporting
confidence: 91%
“…The results of the probit regression revealed that COWN and DOWN showed a negative relationship but not significant with fraud occurrences; thus, it failed to reject the null hypotheses proposed. This finding is consistent with Erickson et al (2006), Zam et al (2014) and Sadique et al (2019), who also documented no evidence that equity incentives are associated with corporate fraud. These results imply that directors' or CEO's share ownership does not influence corporate fraud incidences.…”
Section: Findings and Discussionsupporting
confidence: 86%
See 3 more Smart Citations